Coronary Artery Disease in Rheumatic and Non-Rheumatic Valvular Heart Disease - UzmaGul,AsimJaved,MuhammadAbdusSalamAzad,QaiserKhan, UzmaGul,AsimJaved,MuhammadAbdusSalamAzad,QaiserKhan (Journal of Rawalpindi Medical College, 2018)
Background:To study the prevalence of coronary artery disease (CAD) in patients undergoing valve surgery for rheumatic and non-rheumatic valvular heart disease. Methods: In this cross sectional study, 233 patients planned for valvular heart surgery and aged 40 years or more were subjected to preoperative coronary angiogram. Data regarding risk factors and valve pathology were collected. Continuous variables were presented as mean (SD) and categorical variables as frequencies. Logistic regression analysis was used to study predictive factors for CAD in valvular heart disease. Results: Rheumatic heart disease (RHD) was the commonest etiology; 56% of patients had RHD, while 21% had degenerative valvular heart disease. Mitral stenosis was the most common valve pathology. The overall prevalence of CAD was found to be 31.3% in valvular heart disease (VHD). CAD had a lower prevalence of 18.2% in rheumatic heart disease as compared to a much higher prevalence in degenerative valve disease (62%). Conclusion: CAD has lower prevalence in rheumatic heart disease as compared to degenerative valve disease